Five Breakthroughs: A First Approximation of Brain Evolution From Early Bilaterians to Humans - Bennett, Max S. (Frontiers in Neuroanatomy, 2021)
Retracing the evolutionary steps by which human brains evolved can offer insights on the underlying mechanisms of human brain function as well as the phylogenetic origin of various features of human behavior. To this end, this paper presents a model for interpreting the physical and behavioral modifications throughout major milestones in human brain evolution. This model introduces the concept of a “breakthrough” as a useful tool for interpreting suites of brain modifications and the various adaptive behaviors these modifications enabled. This offers a unique view into the ordered steps by which human brains evolved and suggests several unique hypotheses on the mechanisms of human brain function.